2002
DOI: 10.1001/archopht.120.2.154
|View full text |Cite
|
Sign up to set email alerts
|

Short-Wavelength Sensitivity Deficits in Patients With Migraine

Abstract: To examine short-wavelength sensitivity in patients with migraine using short-wavelength automated perimetry (SWAP) and Stiles 2-color increment threshold procedures. Methods: Twenty-five subjects with migraine with (n=11) and without (n = 14) aura and 20 age-matched headache-free subjects underwent testing. All subjects underwent standard automated perimetry (SAP) and SWAP (using a Humphrey field analyzer; 24-2 presentation pattern). In 2 migraine patients (one with and another without aura), the 2-color incr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
54
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(59 citation statements)
references
References 50 publications
5
54
0
Order By: Relevance
“…Comoglu et al (2003) found glaucomatous-like visual field defects in patients with migraine in the absence of raised intraocular pressures and suggested that there might be a relationship between the pathophysiology of normal tension glaucoma and migraine. McKendrick agreed with this viewpoint (McKendrick et al, 2000(McKendrick et al, , 2002 and concluded that the similarity of SWAP defects and temporally modulated perimetry defects in migraine sufferers and glaucoma sufferers might raise the possibility of a common pre-cortical vascular involvement in these two conditions.…”
Section: Visual Fields and Migrainementioning
confidence: 89%
See 1 more Smart Citation
“…Comoglu et al (2003) found glaucomatous-like visual field defects in patients with migraine in the absence of raised intraocular pressures and suggested that there might be a relationship between the pathophysiology of normal tension glaucoma and migraine. McKendrick agreed with this viewpoint (McKendrick et al, 2000(McKendrick et al, , 2002 and concluded that the similarity of SWAP defects and temporally modulated perimetry defects in migraine sufferers and glaucoma sufferers might raise the possibility of a common pre-cortical vascular involvement in these two conditions.…”
Section: Visual Fields and Migrainementioning
confidence: 89%
“…McKendrick et al (2002) performed short-wavelength automated perimetry (SWAP) and standard automated perimetry (SAP) using a Humphrey Visual Field Analyser. Although they did not find a significant difference in mean deviation and pattern standard deviation between migraine sufferers and controls using SAP, both these parameters were significantly worse in the migraine group using SWAP.…”
Section: Visual Fields and Migrainementioning
confidence: 99%
“…[1][2][3][4][5] This abnormal function does not seem to result from the direct effect of visual aura on cortical visual pathways, because deficits have been reported in subjects who do not experience visual aura as well as in those who do. [1][2][3][4][5][6][7][8] In addition to as well as homonymous defects, which shows cortical involvement, [12][13][14] unilateral nonhomonymous defects were also detected resembling a more localized defect. [1][2][3]5 There is substantial evidence that visual information is transmitted from the retina to cortical area V1 by three pathways that are largely separate, both anatomically and functionally.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8] In addition to as well as homonymous defects, which shows cortical involvement, [12][13][14] unilateral nonhomonymous defects were also detected resembling a more localized defect. [1][2][3]5 There is substantial evidence that visual information is transmitted from the retina to cortical area V1 by three pathways that are largely separate, both anatomically and functionally. These are parvocellular (P), magnocellular (M), and koniocellular (K) pathways.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation